Gauss–Galerkin quadrature rules for quadratic and cubic spline spaces and their application to isogeometric analysis. (January 2017) - Bartoň, Michael; Calo, Victor Manuel
Abstract: We introduce Gaussian quadrature rules for spline spaces that are frequently used in Galerkin discretizations to build mass and stiffness matrices. By definition, these spaces are of even degrees. The optimal quadrature rules we recently derived (Bartoň and Calo, 2016) act on spaces of the smallest odd degrees and, therefore, are still slightly sub-optimal. In this work, we derive optimal rules directly for even-degree spaces and therefore further improve our recent result. We use optimal quadrature rules for spaces over two elements as elementary building blocks and use recursively the homotopy continuation concept described in Bartoň and Calo (2016) to derive optimal rules for arbitrary admissible numbers of elements. We demonstrate the proposed methodology on relevant examples, where we derive optimal rules for various even-degree spline spaces. We also discuss convergence of our rules to their asymptotic counterparts, these are the analogues of the midpoint rule of Hughes et al. (2010), that are exact and optimal for infinite domains. Highlights: We derive optimal quadrature rules for even-degree spline spaces over finite domains. The spaces are used in Galerkin discretizations to build mass and stiffness matrices. The presented methodology handles also spline spaces over non-uniform knot vectors. We investigate the limiting process, as the number of elements goes to infinity. We demonstrate numerically convergence to the asymptotic rule of Hughes et al. (2010).